La teoría de las inteligencias múltiples ¿práctica docente en la educación del Perú? - Jáuregui Salas, Edica Soledad (2016)
The present article starts from a problematic one as a result of the results obtained in the Evaluation Cenal de Estudiantes 2015 (ECE 2015), realized by the Unit of Measurement of the Educational Quality (UMC) of the MINEDU. Reveals that  second grade students perform satisfactorily in the areas of reading and mathematics below 50%. It leads to various concerns in an effort to understand, analyze what actions are not being considered in teaching practice, which makes learners do not reflect the interest and mastery of knowledge. Howard Gardner's theory of multiple intelligences contributes to a broader view of human potentialities, which for many years remained a narrow concept of intelligence. Also, its implication in school contexts.